Autobiographical gaze through Photography (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2021)
There are numerous photographs that refer to the author himself, to the point that, on many occasions, it is difficult to separate the work and the life of the artist. Due to the mimetic capacity of the technical image and the need for the photographer to be present at the scene, photography has been used as a form of memory, even evidence. We could speak of this form of objective gaze, that of the innocent spectator who accepts this image as true or its opposite, through an active, playful spectator, aware of a possible fallacy. To clarify the shadow of doubt that populates the term autobiographical, I start from the hypothesis that autobiography requires a consensus, an intimacy between the creator and the viewer whose value will always depend on the latter interpretation.
Keywords: Autobiography; Gaze; Artistic Photography